Animal Abuse in Egypt: An Assessment of Attitudes, Behaviors and Protective Factors Among University Students and Graduates. - El Saedy, Salma (AUC Knowledge Fountain, 2022)
Animal abuse is an understudied problem in Egypt with possible ramifications on both non-human and human animals and links to interpersonal violence and conduct problems. This study aims to explore the attitudes and behaviors of Egyptian university students and graduates towards the treatment and use of animals in society and to test if exposure to animal abuse is associated with abusive behavior. The study also aims to identify possible protective factors against animal abuse among a group of positive deviants. A mixed-methods approach was used to study these questions; an online survey was disseminated over social media platforms, and 99 respondents from across Egypt completed the survey. From those respondents, eight positive deviants (five women and three men) were interviewed as a step to identify factors that led them to have positive attitudes toward the treatment of animals. The results, obtained by using descriptive statistics, t-tests, and chi-square tests, show relatively positive attitudes of the surveyed respondents towards animal treatment except for the adoption of vegetarian diets. A significant difference between the total attitudes of men and women was found, and a significant correlation was also found between the age of first exposure to animal abuse and committing abusive acts. Eight protective factors were identified from the interviews, including social learning and knowledge about animal sentience and characteristics. The results suggest the possible role of social learning and modeling behavior as drivers of animal abuse among the research participants.